2013
DOI: 10.1016/j.bpj.2012.11.3818
|View full text |Cite
|
Sign up to set email alerts
|

Human AQP1 Is a Constitutively Open Channel that Closes by a Membrane-Tension-Mediated Mechanism

Abstract: This work presents experimental results combined with model-dependent predictions regarding the osmotic-permeability regulation of human aquaporin 1 (hAQP1) expressed in Xenopus oocyte membranes. Membrane elastic properties were studied under fully controlled conditions to obtain a function that relates internal volume and pressure. This function was used to design a model in which osmotic permeability could be studied as a pressure-dependent variable. The model states that hAQP1 closes with membrane-tension i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(58 citation statements)
references
References 46 publications
5
49
0
1
Order By: Relevance
“…This finding adds to the knowledge of the structural basis of AQP gating 17 ; previous experimentally and computationally derived mechanisms proposed that AQP gating involved mechanosensitivity and phosphorylation in yeast AQPs 18 , and membrane tension in both mammalian and yeast AQPs 1921 .…”
Section: Aqp Structure and Functionsupporting
confidence: 52%
“…This finding adds to the knowledge of the structural basis of AQP gating 17 ; previous experimentally and computationally derived mechanisms proposed that AQP gating involved mechanosensitivity and phosphorylation in yeast AQPs 18 , and membrane tension in both mammalian and yeast AQPs 1921 .…”
Section: Aqp Structure and Functionsupporting
confidence: 52%
“…oocytes, but this effect was also observed on water-injected oocytes (Wei et al, 2007). Some evidence supports also the direct role of aquaporins as osmo-or pressure sensors (MacRobbie, 2006;Ozu et al, 2013;Shachar-Hill et al, 2013), as was proposed earlier (Hill et al, 2004). However, there is also ample evidence for the presence and functioning of mechanosensitive ion channels in plant membranes that could transduce pressure signals and affect aquaporins via second messenger systems (Monshausen and Haswell, 2013).…”
Section: Is There a Link Between Changes In Turgor And Water Transpormentioning
confidence: 87%
“…However, isolated membrane vesicles can also show aquaporin-mediated water permeability that is highly dependent on osmotic pressure (Vandeleur et al, 2005). Recently, it has been shown that human AQP1 is constitutively open but closes with increases in membrane tension (Ozu et al, 2013).…”
Section: Is There a Link Between Changes In Turgor And Water Transpormentioning
confidence: 99%
“…Furthermore, gating mechanisms that induce a change in the 3D-channel structure and consequently affect its transport activity [2] have been described for several eukaryotic AQPs [21,22,23,24], among which pH and phosphorylation represent a short-term regulatory mechanism commonly used by several AQP family members [24,25]. However, besides its post-translational modification by phosphorylation, gating mechanisms for AQP5 channel activity regulation have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%